Electrosorption-driven selective thorium removal from radioactive wastewater with phosphate ? Incorporated g-C3N4 electrode - Yussuf N.M.; Ismail A.F.; Rahmat M.A.; Mohamed N.A. (Elsevier Ltd, 2025)
This research introduces a novel approach for developing an improved method for removing thorium ions (Th(IV)), termed as electrosorption, by fusing the principles of electricity and adsorption. The methodology involves utilizing a phosphate ? incorporated graphitic carbon nitride (g-C3N4/P) electrode, synthesized via a hydrothermal ? calcination process with urea as a precursor and bis (2-ethylhexyl) phosphoric acid (D2EHPA) as a dopant. Static batch experiments were conducted to explore the influence of various parameters, including voltages, initial Th(IV) concentrations and operational time, on the electrosorption of Th(IV). Characterization analysis including XRD, FT-IR, FESEM-EDS and XPS were conducted to validate the successful integration of phosphate into the g-C3N4 structure. The g-C3N4/P electrode demonstrated impressive adsorption capacity for Th(IV) electrosorption in an aqueous solution containing an initial concentration of Th(IV) at 100 mg.L?1. It was observed that applying a potential as low as ?0.2 V resulted in significantly increase in the Th(IV) removal with 92.23 % (> 300 mg.g?1) within 30 minutes of duration, compared to cases without the electrochemical assistance (65.41 mg.g?1). Through FT-IR and XPS analyses, the adsorption mechanism was clarified as follows: (1) the negatively charged g-C3N4/P electrode attracted Th(IV) ions through electrostatic interaction; and (2) Th(IV) ions was coordinated with exposed oxygen (O), nitrogen (N) and phosphorus (P) atoms via complexation. In the context of real wastewater scenarios involving rare earth residue, encompassing Ce(III), La(III), Nd(III) and Pr(III) ions, the g-C3N4/P electrode showcased good capabilities in selectively adsorbing Th(IV). Additionally, the electrode synthesized in this study displayed considerable regenerative capabilities, sustaining a commendable removal ratio of approximately 70 % over five successive cycles. These findings underscore the promising potential of g-C3N4/P electrode for thorium removal through electrosorption applications. ? 2024 Elsevier Ltd